Participación ciudadana: una mirada desde el trabajo colaborativo y en red - Correa Cadavid, Carlos Mario; Flórez López, Carlos Alirio; Gallego Castaño, Jazmín Andrea; Arboleda Jaramillo, Carlos Augusto; Garcés Giraldo, Luis Fernando; Jaillier Castrillón, Érika (Corporación Universitaria Americana, 2023)
The Escuela Red de Formación Ciudadana para la Participación is a collaborative learning initiative, where knowledge, experiences and learning are exchanged with the aim of contributing to increase the impact of participation through training. Since its birth in 2015, it was conceived with the intention of providing higher quality citizen training, in order to achieve sustainable impacts and better results in the processes of transformation of the territories. The Network School is a scenario that promotes the construction of a democratic culture based on inclusion, respect, horizontality and dialogue, linking various actors (public servants, academia, social leaders, observers, trainers, social and community organizations, compensation funds and members of other social networks in the City) in order to weave links for cooperation, trust and under the connecting thread that drives to find together better ways to make pedagogy for participation and influence in the territory.